2012
DOI: 10.1038/emboj.2011.487
|View full text |Cite
|
Sign up to set email alerts
|

A molecular mechanism that links Hippo signalling to the inhibition of Wnt/β-catenin signalling

Abstract: The Hippo signalling pathway has emerged as a key regulator of organ size, tissue homeostasis, and patterning. Recent studies have shown that two effectors in this pathway, YAP/TAZ, modulate Wnt/b-catenin signalling through their interaction with b-catenin or Dishevelled, depending on biological contexts. Here, we identify a novel mechanism through which Hippo signalling inhibits Wnt/b-catenin signalling. We show that YAP and TAZ, the transcriptional co-activators in the Hippo pathway, suppress Wnt signalling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
326
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(341 citation statements)
references
References 55 publications
14
326
0
1
Order By: Relevance
“…On the basis of previous observations that both TGF-b and Wnt pathways are regulated by Hippo signaling (16)(17)(18), we determined whether they would be also inhibited by C19. The results indicate that this was the case (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of previous observations that both TGF-b and Wnt pathways are regulated by Hippo signaling (16)(17)(18), we determined whether they would be also inhibited by C19. The results indicate that this was the case (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, evidence from expression studies in patient tumor specimens, transgenic animals, and in vitro experiments, all confirmed inappropriate activation of the canonical Wnt signaling as a major feature in human neoplasia (15). Interestingly, both TGF-b and Wnt signaling were recently found to be regulated by a developmental pathway called Hippo (16)(17)(18). The latter was initially described in drosophila for its ability to control organ size (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that SFKs negatively regulate Wnt-␤-catenin signaling. Given that YAP is thought to inhibit the Wnt-␤-catenin signaling pathway (48)(49)(50), SFKs likely target this pathway through upregulation of YAP activity in crypt IECs. We also found that IEC-specific ablation of Csk increased the number of goblet cells in the ileum as well as in intestinal organoids and that expression of the Notch target genes Olfm4 and Hes1 (9, 51) was downregulated in crypts of Csk CKO mice ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A particularly intriguing intersection is the pathway involving the YAP/TAZ transcriptional regulators, which govern proliferation in a variety of cells and tissues. YAP/ TAZ can be regulated by mechanosensing, a feature that can block its inhibitory kinase, Hippo, and enable YAP/ TAZ to translocate into the nucleus and function as transcriptional cofactors for the TEAD family of DNAbinding proteins (Varelas et al 2010;Heallen et al 2011;Azzolin et al 2012;Imajo et al 2012;Aragona et al 2013). Hippo signaling can also regulate b-catenin, and, reciprocally, YAP/TAZ can inhibit Wnt/b-catenin signaling (Varelas et al 2010;Heallen et al 2011;Imajo et al 2012).…”
Section: Yap/taz and Wnt/b-catenin: Juggling Proliferation Between Twmentioning
confidence: 99%